Intellectual Property and Universality of Reading: Conflict of Interests? - Alfaro López, Héctor Guillermo (2010)
The aim is to clarify the problem of the relationship between intellectual property and the universality of reading, in order to understand whether or not there is a conflict of interests. From the crossing of a synchronic axis, of historical character, with a diachronic axis, of philosophical character: a follow-up is made to explain the deep forces that have given form to the problem dealt with here. It also explains the legal issue of copyright and property rights, which is closely related to the issue at hand. From all this it can be deduced that behind the problem of intellectual property lies the Western historical construction of the figure of subjectivity, which has given rise to the function of "author". The author attributed with the sole authorship of a discourse (work) is a product of the social discourse - a situation that has been historically hidden to which the legal apparatus protecting copyright has contributed. This has led to an antagonism with the universality of reading. In this work, therefore, we have not sought to give an answer to the problem but to make it clearer for its possible solutions.